Pengaruh Tingkat Pertumbuhan, Profitabilitas, Leverage dan Ukuran Perusahaan Terhadap Kebijakan Dividen Perusahaan Makanan dan Minuman : Pengaruh Kinerja Keuangan, Keberagaman Gender, Umur Perusahaan, terhadap Pengungkapan Sustainability Report. - Hari Stiawan; Azzahra Rachma Kinanti (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to analyze and empirically examine the effect of financial performance, gender diversity, and firm age on the disclosure of sustainability reports. This research employs an associative quantitative approach using secondary data obtained from the official website of the Indonesia Stock Exchange and the websites of the respective companies studied. The population of this study includes all energy sector companies listed on the Indonesia Stock Exchange during the 2019–2023 period. The sample selection was carried out using a purposive sampling method based on specific criteria, resulting in 80 company data that met the requirements for analysis. Data analysis was conducted using logistic regression methods with the aid of EViews 12 software to identify relationships and the influence among variables. The results indicate that, partially, financial performance has a significant effect on sustainability report disclosure, while gender diversity and firm age have no significant impact. However, simultaneously, the three variables significantly influence the level of sustainability report disclosure among energy sector companies in Indonesia.